2017
DOI: 10.1097/ccm.0000000000002184
|View full text |Cite
|
Sign up to set email alerts
|

Survival Benefit and Cost Savings From Compliance With a Simplified 3-Hour Sepsis Bundle in a Series of Prospective, Multisite, Observational Cohorts

Abstract: In three independent cohorts, 3-hour bundle compliance was associated with improved survival and cost savings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(101 citation statements)
references
References 26 publications
4
91
1
Order By: Relevance
“…Rhodes revealed a 40% reduction in the odds of sepsis patients dying in the hospital when the ICU was in compliance with the 3-h bundle [21]. Leisman et al revealed that 3-h SSC bundle compliance was associated with improved survival and cost savings [22]. However, our study did not find that increased SSC bundle compliance decreased ICU mortality.…”
Section: Discussioncontrasting
confidence: 74%
“…Rhodes revealed a 40% reduction in the odds of sepsis patients dying in the hospital when the ICU was in compliance with the 3-h bundle [21]. Leisman et al revealed that 3-h SSC bundle compliance was associated with improved survival and cost savings [22]. However, our study did not find that increased SSC bundle compliance decreased ICU mortality.…”
Section: Discussioncontrasting
confidence: 74%
“…While evidence supporting the efficacy of specific 3-hour bundle elements remains unsettled, 19 a wealth of literature demonstrates a correlation between bundle uptake and decreased sepsis mortality, especially for early antibiotic administration. 13,[20][21][22][23][24][25][26] Some analysis suggests that differing initial resuscitation practices explain different mortality rates in the early goal-directed therapy trials. 27 The comparatively poor performance for non-ICU HPS indicates further QI efforts are better focused on inpatient wards, rather than on EDs or ICUs where resuscitation is already delivered with substantially greater fidelity.…”
Section: Discussionmentioning
confidence: 99%
“…Current recommendations from the Surviving Sepsis Campaign suggest resuscitating patients with sepsis-induced hypoperfusion with at least 30 ml/kg of IV crystalloid within the first 3 h [3]. The Surviving Sepsis bundles have been associated with improved survival in numerous largescale studies [4,6,47], although the specific importance of each individual component of the bundle is unclear. It should be noted that while more rapid completion of the 3 h bundle and rapid administration of antibiotics was associated with improved outcome in a study of nearly 50,000 patients, a longer time to completion of initial fluid bolus was not associated with a change in mortality [6].…”
Section: Fluids and Vasopressorsmentioning
confidence: 99%